Roles of Oxytocin in Stress Responses, Allostasis and Resilience - Takayanagi, Yuki; Onaka, Tatsushi (International journal of molecular sciences, 2021)
Oxytocin has been revealed to work for anxiety suppression and anti-stress as well as for psychosocial behavior and reproductive functions. Oxytocin neurons are activated by various stressful stimuli. The oxytocin receptor is widely distributed within the brain, and oxytocin that is released or diffused affects behavioral and neuroendocrine stress responses. On the other hand, there has been an increasing number of reports on the role of oxytocin in allostasis and resilience. It has been shown that oxytocin maintains homeostasis, shifts the set point for adaptation to a changing environment (allostasis) and contributes to recovery from the shifted set point by inducing active coping responses to stressful stimuli (resilience). Recent studies have suggested that oxytocin is also involved in stress-related disorders, and it has been shown in clinical trials that oxytocin provides therapeutic benefits for patients diagnosed with stress-related disorders. This review includes the latest information on the role of oxytocin in stress responses and adaptation.